Three new and two newly recorded species of the water mite genus Arrenurus Dugès, 1834 (Acari, Hydrachnidia: Arrenuridae) from China - Zheng, Yulin; Guo, Jianjun; Zhang, Runzhi (Zootaxa, 2022)
This paper deals with five species of Arrenurus Dugès, 1834 from P. R. China. Arrenurus (Truncaturus) linguaus sp. nov., Arrenurus (Arrenurus) pseudodistinctus sp. nov. and Arrenurus (Arrenurus) yanchengensis sp. nov, are new to science; Arrenurus (Arrenurus) crassicaudatus Kramer, 1875 and Arrenurus (Megaluracarus) ussuriensis Sokolow, 1931 are recorded for the first time for the Chinese fauna. Arrenurus (Truncaturus) linguaus sp. nov. can be distinguished by tongue-shaped hyaline petiole, trapezoid hyaline membrane, and more or less triangular acetabular plates. Arrenurus (Arrenurus) pseudodistinctus sp. nov. can be distinguished by the median of petiole enlarged, obviously wider than the front and rear ends; ligulate process well-developed and fishtail-shaped; hyaline membrane trapezoid. Arrenurus (Arrenurus) yanchengensis sp. nov can be distinguished by a short hyaline membrane and extending to the base of the well-developed pygal lobes; petiole lobes have the same length as the petiole. Detailed descriptions and illustrations of the new and newly recorded species are given in this paper.